Harnessing rhamnolipids from waste glycerol for effective biocontrol of fungal pathogens in cucumber and melon plants - Adnan, Adieya Atyrrah; Ahmad, Khairulmazmi; Pak Dek, Mohd Sabri; Zakaria, Mohd Rafein (Association for Researcher of Skills and Vocational Training, 2024)
Effective postharvest management is essential to maintaining the quality and safety of fruits and vegetables, particularly in preventing decay caused by fungal pathogens. This study explored the potential of rhamnolipids (RLs), a biofungicide derived from waste glycerol, to control fungal infections and enhance the postharvest quality of tomatoes, cucumbers, and mangoes. Initial experiments identified pathogenic fungi impacting these fruits, with Botrytis cinerea, Colletotrichum capsici, and Phytophthora palmivora showing the highest virulence in tomatoes, cucumbers, and mangoes, respectively. However, the primary focus was on evaluating RLs' efficacy in mitigating disease severity and reducing postharvest decay, weight loss, and total soluble solids (TSS) content. RL-treated fruits demonstrated significant improvements in postharvest quality: by day six, RL treatment reduced decay and weight loss in all fruits compared to untreated controls, with RL-treated tomatoes, cucumbers, and mangoes showing decay levels of 22.63%, 15.98%, and 50% respectively, alongside controlled weight loss. Interestingly, RL-treated cucumbers also exhibited an increase in TSS (3.4) even under pathogen pressure, suggesting enhanced sugar content and improved quality. Overall, these findings highlight RLs as a promising biocontrol agent, capable of managing fungal infections while preserving fruit quality during storage. This work underscores the potential of RLs in developing sustainable postharvest interventions against fungal pathogens.